The creation of goal-scoring opportunities at the 2019 FIFA women`s world cup - Kubayi, A. (Journal of Human Kinetics, 2022)
The aim of this study was to analyse how goal-scoring opportunities (GSOs) were created at the 2019 FIFA Women`s World Cup. The sample consisted of 868 GSOs that led to a shot at the goal throughout all 52 games during the tournament. All games were downloaded from the InStat platform. Descriptive statistics, chi-square of association and binary logistic regression analysis were used to analyse the data. Of the 868 GSOs, 81 (9.1%) resulted in goals. A significant association was observed between GSOs and the type of attack (?2=6.38, p=0.01, V=0.09), with more goals being scored from a counter-attack (12.7%) than an organised attack (7.5%). Counter-attacks recorded a higher odds ratio in univariate analysis (OR=0.56; 95%CI:0.35-0.88; p=0.01) than in multivariate analysis (OR=0.46; 95%CI:0.28-0.76; p=0.002). The multivariate analysis further indicated a significant probability of scoring when ball possession started in the middle third of the field (OR=0.19; 95%CI:0.44-0.88; p= 0.01). The current study has practical implications for soccer coaches to develop and implement training sessions to improve goal-scoring chances of women`s teams at international competitions..